Identification of human lactate dehydrogenase A inhibitors with anti-osteosarcoma activity through cell-based phenotypic screening. Issue 4 (15th February 2020) - Wang, Fei; Zhao, Qiheng; Liu, Junzhi; Wang, Zhe; Kong, Daliang
Graphical abstract: Abstract: Human lactate dehydrogenase A plays a key role in the glycolytic process, the inhibition of the enzyme is therefore considered of interest in developing anticancer therapeutics. However, due to the highly polar nature of hLDHA binding pocket, it is very challenge to discover potent cellular active hLDHA inhibitor. Combined a cell-based phenotypic screening assay with a primary enzymatic assay, we discovered three cellular active hLDHA inhibitors, namely 38, 63, and 374, which reduced MG-63 cell proliferation with IC50 values of 6.47, 2.93, and 6.10 µM, respectively, and inhibited hLDHA with EC50 values of 3.03, 0.63, and 3.26 µM, respectively.